Factors influencing management of dry cell battery waste: a case of Greater Accra Region in Ghana - Debrah, Justice Kofi (2024)
Indiscriminate disposal of dry cell battery (DCB) waste contributes to environmental and public health issues in developing countries such as Ghana, due to the toxic nature of this specific waste. Accordingly, a study was conducted in Accra, Ghana, to determine the socio-economic and demographic factors influencing handling DCB waste, aiming a sustainable environment. Using a random sampling technique, a descriptive cross-sectional survey was conducted, encompassing 367 respondents from the Accra-Tema Metropolitan areas and Tema West Municipal Assembly in Greater Accra, Ghana. Using descriptive and multivariate statistical methods, the survey data were analysed with the Statistical Package for Social Sciences (SPSS) version 27. The results of this study show that female gender and residential area are likely to positively influence the use of DCB at home. Education significantly affects the use of DCB and its proper disposal. The results also suggest that 78% of the respondents disposed of DCB waste in waste bins. The mean monthly income of the respondents stands at USD 270, which is average and likely partially to positively influence the disposal of the DCB. The data collected revealed that female gender, age group, family size, and education level influence the indiscriminate disposal of DCB waste and DCB waste recycling. The results highlight that educated females above the age of 55, with a monthly income, are likely to properly segregate DCB waste. This study contributes to the knowledge gap in relation to dry cell battery waste management (DCBWM) in developing countries, aiming to advance global sustainability. This study is expected to contribute to educate and create awareness in managing DCB waste to reduce its indiscriminate disposal which leads to environmental pollution and negatively affects human health and environmental sustainability in Ghana.